Competitiveness of Herbicide-Resistant Waterhemp (Amaranthus tuberculatus) with Soybean. Issue 6 (18th September 2018) - Butts, Thomas R.; Vieira, Bruno C.; Latorre, Débora O.; Werle, Rodrigo; Kruger, Greg R.
Abstract: Waterhemp [ Amaranthus tuberculatus (Moq.) J. D. Sauer] is a troublesome weed occurring in cropping systems throughout the U.S. Midwest with an ability to rapidly evolve herbicide resistance that could be associated with competitive disadvantages. Little research has investigated the competitiveness of different A. tuberculatus populations under similar environmental conditions. The objectives of this study were to evaluate: (1) the interspecific competitiveness of three herbicide-resistant A. tuberculatus populations (2, 4-D and atrazine resistant [2A-R], glyphosate and protoporphyrinogen oxidase [PPO]-inhibitor resistant [GP-R], and 2, 4-D, atrazine, glyphosate, and PPO-inhibitor susceptible [2AGP-S]) with soybean [ Glycine max (L.) Merr.]; and (2) the density-dependent response of each A. tuberculatus population within a constant soybean population in a greenhouse environment. Amaranthus tuberculatus competitiveness with soybean was evaluated across five target weed densities of 0, 2, 4, 8, and 16 plants pot −1 (equivalent to 0, 20, 40, 80, and 160 plants m −2 ) with 3 soybean plants pot −1 (equivalent to 300, 000 plants ha −1 ). At the R1 soybean harvest time, no difference in soybean biomass was observed across A. tuberculatus populations. At A. tuberculatus densities <8 plants pot −1, the 2AGP-S population had the greatest biomass and stem diameter per plant. At the R7 harvest time, the 2AGP-S population caused the greatest loss in soybean biomass and number of pods compared with the other populations at densities of <16 plants pot −1 . The 2AGP-S population had greater early-season biomass accumulation and stem diameter compared with the other A. tuberculatus populations, which resulted in greater late-season reduction in soybean biomass and number of pods. This research indicates there may be evidence of interspecific competitive fitness cost associated with the evolution of 2, 4-D, atrazine, glyphosate, and PPO-inhibitor resistance in A. tuberculatus . Focus should be placed on effectively using cultural weed management practices to enhance crop competitiveness, especially early in the season, to increase suppression of herbicide-resistant A. tuberculatus .